Beach profile data for the Elwha River Delta, 2021-11-04 - Ian Miller (PANGAEA, 2025)
Shoreline topography data were collected using GNSS survey methods, with a differential GPS, typically an AshTech ProMark 200 RTK-DGPS system connected to the Washington State Reference Network, operating in Real Time Kinematic (RTK) mode. Survey data are referenced in the horizontal reference frame to NAD83(2011). Elevations, in meters, are referenced to NAVD88(Geoid09) for all survey data collected before December 2012, NAVD88(Geoid12) for all survey data collected between December 2012 and May 2020, and NAVD88(Geoid18) for all survey data collected subsequently. No conversions were applied to these data to account for variations in horizontal or vertical coordinate system adjustments through time, but an error analysis suggests a standard deviation for the elevations of between 0.03 and 0.05 m across the entire sampling period (2011-2024). All survey data were collected with the GNSS system mounted on a 2.05 m rover pole, held level by a surveyor as a transect line was traced in a cross-shore orientation on the beach. The associated text files include the horizontal (HRMS) and vertical (VRMS) root-mean-square errors estimated by the GNSS system, as well as the RTK-DGPS status reported by the GNSS system at the time each point was collected. Times are referenced to local Pacific time (either PST or PDT).
In: Miller, I (2025): Beach Profile Data for the Elwha River Delta, 2018-2024 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.977774